2010
DOI: 10.1111/j.1365-4632.2010.04660.x
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian online survey to evaluate awareness and treatment satisfaction in individuals with moderate to severe plaque psoriasis

Abstract: A total of 514 panelists completed the survey; 65% reported current moderate/severe/very severe psoriasis. Awareness of available treatment options ranged from 98% for prescription topical agents to 75% for photo/light therapy, and < 50% for prescription oral (49%) or injectable (35%) medications. A total of 92% of respondents had been treated with and 61% were currently taking prescription topical agents. Photo/light therapy had been used by 38% and was currently used by 7% of respondents. Prescribed oral med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 41 publications
3
39
2
2
Order By: Relevance
“…High impact of the treatment modality on satisfaction scores and greatest satisfaction with biologicals were confirmed in regression models controlling for several confounding factors. These results are well in line with several other studies (2,11,12,14,(20)(21)(22) and may be attributed to the high efficacy, favourable risk-benefit profile and convenient application mode of biologicals.…”
Section: Discussionsupporting
confidence: 93%
“…High impact of the treatment modality on satisfaction scores and greatest satisfaction with biologicals were confirmed in regression models controlling for several confounding factors. These results are well in line with several other studies (2,11,12,14,(20)(21)(22) and may be attributed to the high efficacy, favourable risk-benefit profile and convenient application mode of biologicals.…”
Section: Discussionsupporting
confidence: 93%
“…However, for this to be successful, and for patients to be able to properly manage their condition, it is essential that they are fully informed and involved in making choices about their treatment. Yet, in common with other research findings (Poulin et al, 2010), respondents were aware of being under-informed, particularly by their GPs who, as their title suggests, do not have specialist knowledge of the condition nor of all available treatments. Indeed the qualitative data suggested that Psoriasis Association events and newsletters provide much-needed information that is not available to them elsewhere, and yet newly diagnosed patients were rarely given details of this or other skin disorder support organisations.…”
Section: Discussionmentioning
confidence: 77%
“…The tendency of psoriasis and PsA to become chronic represents both a medical and health-economic challenge which underlines the, need for long-term management and in terms of patients longterm outlook [18]. Traditional treatment paradigms involve a stepwise approach in which topical therapies are initially prescribed, followed by phototherapy or light therapy and systemic oral and then injectable agents (biologics) [19,20].…”
mentioning
confidence: 99%